SARS-CoV-2 B.1.617 Mutations L452R and E484Q Are Not Synergistic for Antibody Evasion. (9th September 2021) - Ferreira, Isabella A T M; Kemp, Steven A; Datir, Rawlings; Saito, Akatsuki; Meng, Bo; Rakshit, Partha; Takaori-Kondo, Akifumi; Kosugi, Yusuke; Uriu, Keiya; Kimura, Izumi; Shirakawa, Kotaro; Abdullahi, Adam; et al.
Abstract: The SARS-CoV-2 B.1.617 variant emerged in the Indian state of Maharashtra in late 2020. There have been fears that 2 key mutations seen in the receptor-binding domain, L452R and E484Q, would have additive effects on evasion of neutralizing antibodies. We report that spike bearing L452R and E484Q confers modestly reduced sensitivity to BNT162b2 mRNA vaccine-elicited antibodies following either first or second dose. The effect is similar in magnitude to the loss of sensitivity conferred by L452R or E484Q alone. These data demonstrate reduced sensitivity to vaccine-elicited neutralizing antibodies by L452R and E484Q but lack of synergistic loss of sensitivity.